All carry : a novel - Wojciechowski, Gene (Crown, 2026)
"After the discovery of some old golf clubs at a garage sale, a down-on-his luck reporter discovers they suddenly make him hit perfectly. With the help of disgraced caddy, he competes at the Masters"-- Provided by publisher.